Preparation method of perovskite material, perovskite solar cell and preparation method of perovskite solar cell

The preparation of perovskite materials by inverse temperature crystallization has solved the problems of high-purity raw materials and film defects in the prior art, and the formation and efficient manufacturing of high-purity perovskite films have been achieved, which reduces production costs and improves repeatability.

CN119584826APending Publication Date: 2025-03-07SHENZHEN TECH UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411569239.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-12
Filing Date
2024-11-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the efficient manufacturing process, existing perovskite solar cells face the problems of high-purity raw materials, unstable quality, high production costs, and film defects caused by raw material impurities, which affect the repeatability and efficiency of manufacturing.

Method used

Perovskite materials are prepared by inverse temperature crystallization method. By dissolving multiple substances in an organic solvent and using inverse temperature crystallization method to obtain stable perovskite crystals with accurate stoichiometric ratios, thereby removing impurities in the raw material and obtaining high-purity mixed perovskite crystals.

Benefits of technology

The formation of high-purity perovskite films is achieved, with the increase in grain size and the reduction of surface defects, which inhibits the aging of the precursor solution, greatly extends the shelf life of the solution, reduces production costs, and improves the repeatability and efficiency of manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119584826A_ABST
    Figure CN119584826A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a perovskite material, a perovskite solar cell and a preparation method of the perovskite solar cell, and the method comprises the steps: determining a plurality of substances for synthesizing the perovskite material and the contents of the substances according to the component Cs0. 05FA0. 89MA0. 06Pb (I0. 94Br0. 06) 3 of the perovskite material; dissolving the plurality of substances by adopting an organic solvent to obtain a first solution; and obtaining the perovskite material from the first solution through an inverse temperature crystallization method. In this way, the high-purity mixed perovskite crystal can be obtained, a high-quality perovskite thin film can be formed, the grain size is increased, surface defects are reduced, aging of the precursor solution can be inhibited, and the shelf life of the precursor solution is greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of perovskite solar cells (PSCs), and in particular to a method for preparing a perovskite material, a perovskite solar cell and a method for preparing the same. Background Art

[0002] As a new type of photoactive material, organic-inorganic hybrid perovskite has excellent photovoltaic properties such as high light absorption coefficient, excellent carrier mobility, extended carrier diffusion length, low exciton binding energy and adjustable band gap, which makes it have broad research and application value in the field of solar cells. At present, the mainstream high-efficiency perovskite solar cell light absorption layer is mainly prepared by directly mixing extremely high-purity lead halide and organic ammonium salt in polar solvents. However, extremely high-purity raw materials are expensive and of unstable quality, which leads to a significant increase in production costs and hinders the repeatability of high-efficiency perovskite solar cell manufacturing; in addition, impurity elements in the raw materials are also one of the factors that cause defects in perovskite films. Summary of the invention

[0003] Based on this, the embodiments of the present application provide a method for preparing a perovskite material, a perovskite solar cell and a method for preparing the same, which can obtain high-purity mixed perovskite crystals, which is conducive to the formation of high-quality perovskite films, increase the grain size, reduce surface defects, and inhibit the aging of the precursor solution, greatly extending the shelf life of the precursor solution.

[0004] In a first aspect, the present application provides a method for preparing a perovskite material, the preparation method comprising:

[0005] According to the component Cs of the perovskite material 0.05 FA 0.89 MA 0.06 Pb(I 0.94 Br 0.06 )3, determining a plurality of substances and their contents for synthesizing the perovskite material;

[0006] Dissolving the plurality of substances in an organic solvent to obtain a first solution;

[0007] The perovskite material is obtained from the first solution by a temperature inversion crystallization method.

[0008] In a second aspect, the present application provides a perovskite solar cell, wherein the perovskite light absorption layer of the perovskite solar cell includes the perovskite material prepared as described in the first aspect above.

[0009] In a third aspect, the present application provides a method for preparing a perovskite solar cell, the preparation method comprising:

[0010] Providing a transparent conductive glass substrate;

[0011] Preparing an electron transport layer on the transparent conductive glass substrate;

[0012] A perovskite light absorption layer is prepared on the electron transport layer using a perovskite precursor solution, wherein the perovskite precursor solution is prepared using the perovskite material prepared in the first aspect as described above;

[0013] Preparing a hole transport layer on the perovskite light absorption layer to obtain a prefabricated device;

[0014] A metal electrode is prepared on the prefabricated device to obtain the perovskite solar cell.

[0015] The embodiments of the present application provide a method for preparing a perovskite material, a perovskite solar cell and a method for preparing the same. Non-high-purity raw materials are used and an inversion crystallization method is adopted to obtain stable perovskite crystals with an accurate stoichiometric ratio. The process can remove impurities contained in the raw materials and obtain high-purity mixed perovskite crystals. The stability of the configured perovskite precursor solution is significantly better than that of the precursor solution directly prepared from the raw materials. It is not only conducive to the formation of high-quality perovskite films, but also increases the grain size and reduces surface defects. It can also inhibit the aging of the precursor solution and greatly extend the shelf life of the solution. The perovskite material preparation method is simple, has stable performance, and can be industrialized. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a schematic diagram of a process of an embodiment of a method for preparing a perovskite material of the present application;

[0017] Figure 2 It is a schematic flow chart of another embodiment of the method for preparing the perovskite material of the present application;

[0018] Figure 3 It is a schematic flow chart of another embodiment of the method for preparing the perovskite material of the present application;

[0019] Figure 4 It is a schematic diagram of a process of an embodiment of a method for preparing a perovskite solar cell of the present application;

[0020] Figure 5 It is a dynamic light scattering DLS schematic diagram and ultraviolet visible light UV-Vis schematic diagram of the perovskite precursor solution of the embodiment of the present application and the precursor solution of the control group;

[0021] Figure 6 is the XRD spectrum of the perovskite light absorbing layer of the embodiment of the present application and the perovskite light absorbing layer of the control group;

[0022] Figure 7is a SEM picture of the perovskite light absorbing layer of the embodiment of the present application and the perovskite light absorbing layer of the control group;

[0023] Figure 8 is a schematic diagram of the particle size distribution of the perovskite crystals of the perovskite light absorbing layer of the embodiment of the present application and the perovskite crystals of the perovskite light absorbing layer of the control group;

[0024] Fig. 9 SSPL schematic diagram and TRPL schematic diagram of the perovskite light absorbing layer of the embodiment of the present application and the perovskite light absorbing layer of the control group;

[0025] Fig.10 It is a schematic diagram of the JV characteristic curve, Nyquist diagram, short-circuit current density-light intensity diagram, open-circuit voltage-light intensity diagram, and a schematic diagram of the results of the space charge limited current test of the perovskite solar cell of the embodiment of the present application and the perovskite solar cell of the control group;

[0026] Fig.11 Schematic diagram of current density-voltage of the perovskite solar cell of the embodiment of the present application and the perovskite solar cell of the control group, and schematic diagram of current density-voltage under forward scanning and reverse scanning states;

[0027] Fig.12 It is a schematic diagram of the EQE-wavelength curve, a schematic diagram of the current density and PCE-time, and a schematic diagram of the normalized PCE-time of the perovskite solar cell of the embodiment of the present application and the perovskite solar cell of the control group;

[0028] Fig.13 It is a schematic diagram of PCE-aging time of the perovskite precursor solution of the embodiment of the present application and the perovskite precursor solution of the control group. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0030] The flowcharts shown in the accompanying drawings are only examples and do not necessarily include all the contents and operations / steps, nor must they be executed in the order described. For example, some operations / steps may also be decomposed, combined or partially merged, so the actual execution order may change according to actual conditions.

[0031] Perovskite in a narrow sense refers to the mineral CaTiO3, while in a broad sense, it refers to ABX3 type compounds with a perovskite structure. The perovskite light absorption layer in a perovskite solar cell usually refers to an organic / inorganic metal halide ABX3. A represents a monovalent organic or inorganic cation (such as methylamine ion CH3NH3 + , Cesium ion Cs + 、Rubidium ion Rb + etc.); B represents a divalent metal cation (such as lead ion Pb 2+ 、Sn 2+ 、Ge 2+ ); X represents a monovalent halogen anion (such as bromide ion Br - 、Iodide ion I - 、Chloride ion Cl - ). The working principle of perovskite solar cells is similar to that of crystalline silicon cells. The physical process of photoinduced electromotive force is as follows: after the perovskite light absorption layer absorbs photons, electrons absorb energy and jump from the valence band to the conduction band to form electron-hole pairs; the electrons and hole pairs are quickly separated inside the light absorption layer and transported to the cathode and anode through the electron transport layer (ETL) and hole transport layer (HTL), respectively. As electrons and holes accumulate at the anode and cathode, photoinduced electromotive force is generated between the two poles, thereby generating photocurrent.

[0032] Organic-inorganic hybrid perovskites are novel photoactive materials with excellent photovoltaic properties such as high light absorption coefficient, excellent carrier mobility, extended carrier diffusion length, low exciton binding energy and adjustable band gap, which make them have broad research and application value in the field of solar cells. Recently, partial substitution of A, B or X sites of perovskite materials with corresponding elements or molecular analogs has become the focus, providing a promising way to prepare efficient and stable perovskite solar cells. The mainstream high-efficiency perovskite solar cell light absorption layer is mainly prepared by directly mixing extremely high-purity lead halide and organic ammonium salt in polar solvents. However, extremely high-purity raw materials are expensive, raw material storage conditions are harsh, sensitive to humidity and oxygen in the environment, and raw material quality is unstable and varies from batch to batch, which leads to a significant increase in production costs and hinders the repeatability of efficient perovskite solar cell manufacturing; in addition, impurity elements in the raw materials cause defects in the perovskite film, and the difference in solubility of the raw materials makes it difficult to maintain an accurate stoichiometric ratio in the precursor solution, and the precursor solution directly mixed with the raw materials has a short shelf life.

[0033] The embodiment of the present application proposes a method for preparing a perovskite material, which uses non-high-purity raw materials and an inversion crystallization method to obtain stable perovskite crystals with an accurate stoichiometric ratio. The process can remove impurities contained in the raw materials and obtain high-purity mixed perovskite crystals. The stability of the configured perovskite precursor solution is significantly better than that of the precursor solution directly prepared from the raw materials. It is not only conducive to the formation of high-quality perovskite films, but also increases the grain size and reduces surface defects. It can also inhibit the aging of the precursor solution and greatly extend the shelf life of the solution. The perovskite material preparation method is simple, has stable performance, and can be industrialized.

[0034] The embodiments of the present application are described in detail below with reference to the accompanying drawings.

[0035] See also Figure 1 , Figure 1 It is a flow chart of an embodiment of a method for preparing a perovskite material of the present application, wherein the preparation method comprises: steps S101 to S103.

[0036] Step S101: According to the component Cs of the perovskite material 0.05 FA 0.89 MA 0.06 Pb(I 0.94 Br 0.06 )3. Determine multiple substances and their contents for synthesizing the perovskite material.

[0037] In the embodiment of the present application, the components of the perovskite material include Cs 0.05 FA 0.89 MA 0.06 Pb(I 0.94 Br 0.06 )3, so the multiple substances used to synthesize the perovskite material can be determined based on the component, and the required content of each substance can be calculated in combination with the amount of synthesized perovskite material. In this way, stable perovskite crystals with accurate stoichiometric ratios can be obtained.

[0038] In some embodiments, the plurality of substances include: PbI2, FAI (formamidine hydroiodide, also known as formamidine iodine), MABr (methylammonium bromide, chemical formula CH3NH3Br), PbBr2 and Cs I. The plurality of substances used to synthesize the perovskite material in the embodiments of the present application are relatively easy to obtain and common substances on the market.

[0039] Step S102: using an organic solvent to dissolve the plurality of substances to obtain a first solution.

[0040] These multiple substances need to be dissolved in an organic solvent to obtain a first solution.

[0041] In some embodiments, the organic solvent includes GBL (i.e., γ-butyrolactone) and formic acid. In practical applications, a plurality of the substances can be first dissolved with GBL, stirred at room temperature until the solution is clear, and then formic acid is added, and stirred continuously until the solution is completely dissolved.

[0042] Step S103: obtaining the perovskite material from the first solution by a temperature inversion crystallization method.

[0043] Inversion crystallization is a commonly used chemical separation technology. It uses the difference in solubility of substances at different temperatures to separate substances by controlling the temperature. Inversion crystallization is a method of precipitating crystals by using the phenomenon that the solubility of solutes in solutions decreases as the temperature increases. Inversion crystallization can grow high-quality single crystals. If the purity of multiple substances is not high and contains impurity elements, then in this way, the impurity elements contained in the multiple substances can be separated from the perovskite material synthesized by the crystallization of the multiple substances, the impurities contained in the raw materials of the multiple substances can be removed, and high-purity mixed perovskite crystals can be obtained.

[0044] Therefore, the embodiments of the present application can utilize non-high-purity raw materials, which can reduce costs and avoid the following problems caused by the use of extremely high-purity raw materials: harsh storage conditions for raw materials, sensitivity to humidity and oxygen in the environment, unstable quality of raw materials, and variations from batch to batch, which leads to a significant increase in production costs and hinders the repeatability of the manufacture of efficient perovskite solar cells.

[0045] See also Figure 2 In some embodiments, step S103, before obtaining the perovskite material from the first solution by the inversion crystallization method, may also include: step S104.

[0046] Step S104: filtering the first solution using a nylon filter membrane.

[0047] At this time, step S103, obtaining the perovskite material from the first solution by an inversion crystallization method, may include: obtaining the perovskite material from the filtered first solution by an inversion crystallization method.

[0048] In order to remove undissolved impurities as much as possible in the embodiment of the present application, before the inversion crystallization, the first solution is filtered using a nylon filter membrane (for example, with a pore size of 0.45 μm), and the filtrate is subjected to inversion crystallization after filtration.

[0049] See also Figure 3 In some embodiments, step S103, obtaining the perovskite material from the filtered first solution by the inversion crystallization method, may also include: sub-steps S1031 to S1033.

[0050] Sub-step S1031: keeping the filtered first solution in an oil bath at a preset temperature (for example, the temperature of the oil bath is in the range of 90° C. to 110° C.) until the perovskite crystals are completely precipitated.

[0051] Sub-step S1032: washing the precipitated perovskite crystals and then drying them.

[0052] In practical applications, the precipitated perovskite crystals can be placed on a clean dust-free cloth to absorb the residual solvent, rinsed with ethyl acetate, and then transferred to a hot stage for further drying.

[0053] Sub-step S1033: Grinding the dried perovskite crystals into powder and continuing to dry to obtain powdered perovskite crystals.

[0054] The dried perovskite crystals can be ground into powder using a mortar and then transferred to a glove box and continued to dry on a hot stage (for example, continue drying for 30 minutes), and finally obtain black powdered perovskite crystals, which are the perovskite materials of the embodiments of the present application.

[0055] In the embodiment of the present application, the precipitated perovskite crystals are washed and dried, and then ground into powder and dried again. In this way, the residual solvent can be further removed and the purity of the perovskite crystals can be improved.

[0056] The present application also provides a perovskite solar cell, wherein the perovskite light absorption layer of the perovskite solar cell comprises a perovskite material obtained by any of the above preparation methods. For a detailed description of the relevant content, please refer to the preparation method of the above perovskite material, which will not be repeated here.

[0057] Perovskite solar cells are highly efficient photoelectric conversion devices based on perovskite materials. Its structure mainly consists of five key parts, including transparent conductive glass substrate, electron transport layer ETL, perovskite light absorption layer, hole transport layer HTL and metal electrode. The electron transport layer ETL must meet the requirements of good contact with the perovskite light absorption layer, so that the potential barrier of electrons in the transmission process is reduced, and the holes are prevented from being transmitted to the cathode while completing the electron transmission; currently, mesoporous layer structures are mostly used, which can be TiO2 or Al2O3, etc., and can also play a structural support role. The hole transport layer HTL needs to have a good heterojunction contact interface with the perovskite light absorption layer to reduce the potential barrier in the hole transmission process, complete the hole transmission and prevent the electrons from moving to the anode; the hole transport layer can be organic (such as Spiro-OMeTAD small molecule materials, triphenylamine, etc.), or inorganic compounds (such as copper iodide, nickel oxide, etc.). The transparent conductive glass substrate generally uses commercial ITO (indium tin oxide) or FTO oxide (fluorine-doped tin oxide) conductive glass, which has a transmittance of up to 80-90% in the visible light band, strong conductivity, and suitable work function. The perovskite light absorption layer is used to absorb light and generate electron-hole pairs, usually organic metal halides.

[0058] In some embodiments, the electron transport layer of the perovskite solar cell includes a SnO2 electron transport layer, and the hole transport layer of the perovskite solar cell includes a Spiro-OMeTAD hole transport layer.

[0059] The materials most commonly used to prepare electron transport layers (ETLs) are oxide semiconductors such as TiO2, ZnO, and SnO2. Among all these materials, SnO2 has advantages such as a wider band gap, high transmittance in the visible light range, high electron mobility, and low conduction band offset, making it more suitable for use as ETL.

[0060] Spiro-OMeTAD is 2,2',7,7'-tetrakis[n,n-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene. As a solid-state hole transport material, Spiro-OMeTAD can greatly improve the photoelectric conversion efficiency and stability of perovskite solar cells, and promote the rapid development of perovskite solar cells. At present, the photoelectric conversion efficiency of perovskite solar cells using Spiro-OMeTAD as a hole transport material has exceeded 28.57%, which is comparable to traditional silicon-based solar cells and thin-film solar cells such as cadmium telluride, and has good development prospects.

[0061] See also Figure 4 , Figure 4 It is a flow chart of an embodiment of a method for preparing a perovskite solar cell of the present application, and the preparation method comprises: step S201 to step S205.

[0062] Step S201: providing a transparent conductive glass substrate.

[0063] Transparent conductive glass substrates usually use conductive glass coated with tin oxide (SnO2), indium tin oxide (ITO) or FTO oxide (fluorine-doped tin oxide). It has good transparency and conductivity and can be used as a light transmission medium and bottom electrode.

[0064] Step S202: preparing an electron transport layer on the transparent conductive glass substrate.

[0065] The electron transport layer is located between the perovskite light absorption layer and the bottom electrode. Commonly used materials include titanium dioxide (TiO2), zinc oxide (ZnO), or SnO2. The main function of the electron transport layer is to accept electrons from the perovskite light absorption layer and transfer them to the bottom electrode. It has good electron conduction performance and band matching characteristics, which helps to improve the collection efficiency and transmission speed of electrons.

[0066] In some embodiments, since SnO 2 has advantages such as a wider band gap, high transmittance in the visible light range, high electron mobility, and low conduction band offset, the electron transport layer includes a SnO 2 electron transport layer.

[0067] Step S203: preparing a perovskite light absorption layer on the electron transport layer using a perovskite precursor solution, wherein the perovskite precursor solution is prepared using a perovskite material prepared by any of the above preparation methods.

[0068] The perovskite light absorption layer is a key component of the perovskite solar cell. The layer has excellent light absorption characteristics and photoelectric conversion efficiency, and can convert incident photons into charge carriers. The perovskite material used in the embodiment of the present application is a perovskite material obtained by the above-mentioned preparation method of the perovskite material, and then the perovskite material is configured to obtain a perovskite precursor solution, and the perovskite precursor solution is used to prepare the perovskite light absorption layer on the electron transport layer.

[0069] Step S204: preparing a hole transport layer on the perovskite light absorption layer to obtain a prefabricated device.

[0070] The hole transport layer is located between the perovskite light absorption layer and the top electrode. Commonly used materials include organic semiconductor materials, such as poly (3,4-ethylenedioxythiophene) (PEDOT:PSS), Spiro-OMeTAD, etc. The function of the hole transport layer is to accept holes in the perovskite light absorption layer and transfer them to the top electrode. The hole transport layer has good hole transport properties and light stability, which helps to improve the collection efficiency and transmission speed of holes.

[0071] In some embodiments, since Spiro-OMeTAD, as a solid-state hole transport material, can greatly improve the photoelectric conversion efficiency and stability of perovskite solar cells, the hole transport layer includes a Spiro-OMeTAD hole transport layer.

[0072] Step S205: preparing a metal electrode on the prefabricated device to obtain the perovskite solar cell.

[0073] Metal electrodes are usually located at the top and bottom of perovskite solar cells. Common metals used for metal electrodes here include gold (Au), silver (Ag), aluminum (Al) or copper (Cu). The main function of metal electrodes is to collect electrons (bottom electrode) and holes (top electrode) and guide them to the external circuit. Metal electrodes have good electrical conductivity and light reflection properties to reduce energy loss and increase current output.

[0074] In some embodiments, the metal electrode includes a gold electrode because the gold electrode has excellent electrical conductivity.

[0075] The rational design and optimization of the structures of these components of the above-mentioned perovskite solar cells can achieve efficient light absorption, effective separation of electrons and holes, and rapid transport of carriers in perovskite solar cells, thereby improving the energy conversion efficiency of solar cells.

[0076] In some embodiments, step S203, before preparing the perovskite light absorption layer on the SnO2 electron transport layer using the perovskite precursor solution, may further include: step S206.

[0077] Step S206: The perovskite precursor solution is obtained by configuring the perovskite material prepared by any of the above methods.

[0078] In the embodiment of the present application, if the perovskite precursor solution is not prepared in advance, it is necessary to first prepare the perovskite precursor solution using the perovskite material prepared by any of the above methods.

[0079] In some embodiments, step S206, configuring the perovskite material prepared by any of the above methods to obtain the perovskite precursor solution may include: dissolving the perovskite material prepared by any of the above methods and MACl in a mixed solvent of DMF (dimethylformamide) and DMSO (dimethyl sulfoxide) to obtain the perovskite precursor solution.

[0080] Common solvents for preparing perovskite precursor solutions include dimethylformamide (DMF), G-butyrolactone (GBL), dimethyl sulfoxide (DMSO) and N,N-dimethylacetamide (DMA). The above polar solvents can be removed by thermal annealing or drying in air and an inert atmosphere. During the solvent removal process, the perovskite material is supersaturated, thus causing its nucleation and crystal growth. This method is a simple and easy perovskite deposition solvent evaporation method. In the embodiment of the present application, a mixed solvent of DMF and DMSO is used to prepare the perovskite precursor solution.

[0081] Perovskite precursor solutions are usually colloidal dispersions rather than true solutions. More specifically, perovskite precursor solutions are colloids formed by a stable colloidal skeleton; this lead-based polyhalide skeleton is formed by the inorganic and organic components in the precursor sharing halogen atoms through coordination; the morphology and size of this skeleton determine the morphology and grain size of the perovskite after solution spin coating and annealing. When the additive MACl (methylammonium chloride) is added, the tetragonal skeleton is retained and further grown, and the skeleton is more stable. During the annealing process, MACl is more volatile and the plane spacing of the framework is larger, which accelerates the crystallization process. Therefore, adding the additive MACl when configuring the perovskite precursor solution can control the perovskite crystallization process, improve the crystallization morphology of the perovskite, and increase the surface coverage; the perovskite film with a specific crystal orientation obtained by post-treatment with MACl can significantly improve the performance of perovskite solar cells, and the average photoelectric conversion efficiency (PCE) of perovskite solar cells can be increased by 26%.

[0082] The following is a detailed description of the method for preparing the above-mentioned perovskite material of the present application, the perovskite material prepared thereby, the method for preparing a perovskite solar cell, and the perovskite solar cell using a specific embodiment.

[0083] 1. Preparation process of perovskite crystallization and perovskite precursor solution:

[0084] 1. Determine the synthetic component as Cs 0.05 FA 0.89 MA 0.06 Pb(I 0.94 Br 0.06 )3. Dissolve 507 mg PbI2, 172 mg FAI, 7.5 mg MABr, 24.6 mg PbBr2, and 13 mg CsI in each ml of GBL, stir at room temperature until the solution is clear, then add 2% by volume formic acid and continue stirring until it is completely dissolved.

[0085] 2. Filter the solution in step 1 through a nylon filter membrane (pore size 0.45 μm) into a crystallization dish. The oil bath temperature is between 90°C and 110°C, and the temperature is maintained until the perovskite crystals are completely precipitated.

[0086] 3. Take out the crystals precipitated in step 2, place them on a clean dust-free cloth to absorb the residual solvent, rinse the crystals with ethyl acetate, and then transfer them to a hot plate for further drying. Grind the dried crystals into powder with a mortar, transfer them to a glove box and continue drying on a hot plate for 30 minutes; finally, a black powdery perovskite crystal is obtained.

[0087] 4. Preparation of the perovskite precursor solution of the embodiment of the present application: Weigh 1086 mg of the black powdered perovskite crystals obtained in step 3 and 35 mg of MACl, dissolve them in a mixed solvent of DMF / DMSO (volume ratio 8:1), and stir overnight for use.

[0088] Preparation of precursor solution for the control group: weigh the raw materials (i.e., 507 mg PbI2, 172 mg FAI, 7.5 mg MABr, 24.6 mg PbBr2, 13 mg CsI) and directly dissolve them in a mixed solvent of DMF / DMSO (volume ratio 8:1).

[0089] Dynamic light scattering (DLS) analysis and ultraviolet-visible spectroscopy (UV-Vis) analysis were performed on the perovskite precursor solution of the embodiment of the present application and the precursor solution of the control group. The results are as follows: Figure 5 As shown. Figure 5 As can be seen from the left figure, the diameter of the colloidal particles of the perovskite precursor solution of the embodiment of the present application is larger than the diameter of the colloidal particles of the precursor solution of the control group. Figure 5 As can be seen from the right figure, the absorbance of the perovskite precursor solution of the embodiment of the present application to ultraviolet light (less than 450nm) is significantly greater than the absorbance of the precursor solution of the control group to ultraviolet light.

[0090] 2. Preparation process of perovskite solar cells:

[0091] 1. Substrate cleaning: Select FTO (specification, 20*16*2.2mm) transparent conductive glass substrate, scrub with soapy water and rinse the surface with deionized water. Then ultrasonically clean it in deionized water, acetone, and isopropanol for 15 minutes. After drying the substrate surface with a nitrogen gun, perform UV ozone treatment for 15 minutes to enhance surface wettability.

[0092] 2. Electron transport layer (ETL) deposition: SnO2 colloid solution and deionized water were mixed in a volume ratio of 1:4 to make SnO2 precursor solution. 80 μL of SnO2 precursor solution was evenly dropped on the FTO glass substrate, spin-coated at 4000 rpm for 30 seconds, and annealed at 150°C for 40 minutes. Then, UV-ozone treatment was also performed for 15 minutes and quickly transferred to the glove box.

[0093] 3. Deposition of perovskite light absorption layer: 60 μL of perovskite precursor solution was evenly dripped onto the surface of the ETL layer, and the uniform coating process was completed by two-step spin coating (1000 rpm, 5s and then 5000 rpm, 25s). 300 μL of ethyl acetate (anti-solvent) was quickly dripped onto the surface of the perovskite liquid film 20 seconds after the start of spin coating. After this process, the FTO glass substrate was transferred to a hot stage and annealed at 150°C for 10 minutes.

[0094] Deposition of perovskite light absorbing layer of control group: The above perovskite precursor solution was replaced with the precursor solution of the control group, and the other steps were the same.

[0095] X-ray diffraction (XRD) and scanning electron microscope (SEM) analysis were performed on the perovskite light absorbing layer of the embodiment of the present application and the perovskite light absorbing layer of the control group. The results are as follows: Figure 6 , Figure 7 shown.

[0096] pass Figure 6 It can be seen from the XRD spectrum that after X-ray irradiation, the light intensity scattered by the perovskite film of the perovskite light absorbing layer of the embodiment of the present application is greater than the light intensity scattered by the perovskite film of the perovskite light absorbing layer of the control group, and the perovskite film of the perovskite light absorbing layer of the control group also scatters an impurity peak (at the five-pointed star mark in the figure, it was detected that the impurity peak was generated by PbI2).

[0097] pass Figure 7 The SEM image on the left shows that the grain size of the perovskite film in the control group's perovskite light absorption layer is uneven, and the average grain size is small. Figure 7 As can be seen from the SEM image on the right, the grain size of the perovskite film of the perovskite light absorption layer of the embodiment of the present application is relatively uniform, and the average grain size is relatively large.

[0098] See also Figure 8 , Figure 8 Schematic diagram of the grain size distribution of the perovskite film of the perovskite light absorbing layer of the control group and the perovskite film of the perovskite light absorbing layer of the embodiment of the present application. Figure 8As can be seen from the left figure, the average grain size of the perovskite film in the control group's perovskite light absorption layer is less than 600nm. Figure 8 As can be seen from the right figure, the average grain size of the perovskite film of the perovskite light absorption layer of the embodiment of the present application is about 800nm.

[0099] 4. After the substrate in step 3 was cooled to room temperature, 50 μL of BAI solution (1 mg / mL dissolved in isopropanol) was spin-coated at 4000 rpm for 30 s onto the surface of the crystallized perovskite film to passivate surface defects, and then immediately transferred to a hot stage for annealing at 100 °C for 10 min.

[0100] 5. Hole transport layer (HTL) deposition:

[0101] i) Preparation of HTL solution: 75 mg of Spiro-OMeTAD was dissolved in 1 mL of chlorobenzene, and doped with 28.5 μL of tBP and 17.5 μL of Li-TFSI (520 mg / mL dissolved in acetonitrile), and mixed well.

[0102] ii) 80 μL of the HTL solution was dropped onto the FTO glass substrate cooled to room temperature (in step 4), and spin-coated at 4000 rpm for 30 s to obtain a prefabricated device, which was stored in a vacuum oven for oxidation for 12 hours.

[0103] 6. Gold electrode evaporation: Transfer the fully oxidized prefabricated device to the vacuum coating machine, and the vacuum degree in the chamber reaches 3x10 -5 After Pa, the gold electrode was evaporated to a thickness of 80nm. The effective area of ​​the perovskite solar cell is 0.06cm 2 .

[0104] like Fig. 9 As shown, the charge transport performance was analyzed by steady-state photoluminescence (SSPL) and time-resolved photoluminescence (TRPL) spectroscopy.

[0105] (1) Fig. 9 The three figures above illustrate that in the case of only conductive glass, electron transport layer SnO2, and perovskite light absorption layer (Perovskite, abbreviated as PVK), the laser is excited from one side of the perovskite light absorption layer. The fluorescence intensity and fluorescence lifetime of the perovskite light absorption layer of the embodiment of the present application are greater than the fluorescence intensity and fluorescence lifetime of the perovskite light absorption layer of the control group. This shows that the perovskite light absorption layer of the embodiment of the present application has stronger photoluminescence and longer carrier lifetime, which is due to the better crystallinity of the perovskite in the embodiment of the present application.

[0106] (2) Fig. 9 The three middle figures illustrate: in the case of only conductive glass, electron transport layer SnO2, and perovskite light absorption layer, the laser is excited from the conductive glass side, and the fluorescence intensity and fluorescence lifetime of the perovskite light absorption layer of the embodiment of the present application are both lower than those of the perovskite light absorption layer of the control group. This indicates that the charge extraction on the interface of the perovskite light absorption layer of the embodiment of the present application is faster because the perovskite light absorption layer interface and the electron transport layer SnO2 interface of the embodiment of the present application have fewer defects.

[0107] (3) Fig. 9 The following three figures illustrate: in the case of only conductive glass and perovskite light absorbing layer (missing electron transport layer SnO2), laser is excited from one side of the perovskite light absorbing layer, the fluorescence intensity of the perovskite light absorbing layer of the embodiment of the present application is much greater than the fluorescence intensity of the perovskite light absorbing layer of the control group, and the fluorescence lifetime of the perovskite light absorbing layer of the embodiment of the present application is not much different from that of the perovskite light absorbing layer of the control group, which indicates that the perovskite light absorbing layer of the embodiment of the present application has stronger photoluminescence and longer carrier lifetime. This is because the perovskite of the embodiment of the present application has better crystallinity and the influence of the electron transport layer SnO2 on the photoluminescence of the perovskite light absorbing layer of the embodiment of the present application is eliminated.

[0108] like Fig.10 As shown, the photoelectric performance of perovskite solar cells is analyzed by the current density-voltage (JV) characteristic curve (upper left figure) and the Nyquist diagram (upper right figure).

[0109] The most important metric for solar cells is the photoelectric conversion efficiency (PCE). The specific performance parameters of the photoelectric conversion efficiency include: fill factor (FF), open circuit voltage (V OC ) and short-circuit current density (J SC ), in order to achieve higher photoelectric conversion efficiency, it is necessary to achieve higher FF, V OC and J SC The photovoltaic characteristics can be intuitively represented by the JV curve: the value of the intersection of the curve and the vertical axis is J SC , represents the short-circuit current density of the solar cell, and the value of the intersection of the curve and the horizontal axis is V OC , represents the open circuit voltage of the solar cell. The photoelectric conversion efficiency of a solar cell is the ratio of the output power of the solar cell to the incident light power of the sun.

[0110] Electrochemical impedance spectrum and fitting curve equivalent circuit diagram, also known as Nyquist diagram. Perovskite solar cells can be equivalent to the circuit shown in the figure. The smaller the series resistance Rs of the theoretically ideal photovoltaic device, the larger the parallel resistance Rrec, which can make the overall resistance value in the working state lower, and the more conducive to the transmission and extraction of charge. It can be seen from the upper right figure that the Rs of the perovskite solar cell of the embodiment of the present application is smaller than the Rs of the perovskite solar cell of the control group, and the Rrec of the perovskite solar cell of the embodiment of the present application is larger than the Rrec of the perovskite solar cell of the control group, which shows that the perovskite solar cell of the embodiment of the present application can help enhance the charge extraction capability.

[0111] from Fig.10 The short-circuit current density-light intensity (J SC -Light intensity) graph shows that as the light intensity increases, the short-circuit current density of the perovskite solar cell increases linearly, and the fitting straight lines of the two perovskite solar cells basically coincide with each other. The ideal factor of the perovskite solar cell in the control group is 0.979, and the ideal factor of the perovskite solar cell in the embodiment of the present application is 0.985.

[0112] from Fig.10 The open circuit voltage-light intensity (V OC -Light intensity) graph shows that the open circuit voltage of the two perovskite solar cells increases linearly with the increase of light intensity; however, under any same light intensity, the open circuit voltage of the perovskite solar cell of the embodiment of the present application is greater than the open circuit voltage of the perovskite solar cell of the control group. The slope of the fitted straight line of the perovskite solar cell of the embodiment of the present application is 1.46kT / q, and the slope of the fitted straight line of the perovskite solar cell of the control group is 1.61kT / q.

[0113] Fig.10 The lower left and lower right figures are the result diagrams of the space charge limited current test. The structure diagram of the hole defect state density of the test battery in the lower left figure is: Ag (silver), PCBM (fullerene derivative, electron transport layer), PVK (perovskite), SnO2 (tin dioxide), FTO (fluorine-doped tin oxide), and the structure diagram of the electron defect state density of the test battery in the lower right figure is: Au (gold), PVK (perovskite), PTAA (polytriphenylamine, hole transport layer), I TO (indium tin oxide). It can be seen from the figure that the trap filling limit voltage V of the perovskite film of the embodiment of the present application is TFL (0.31V, 0.75V) are higher than the trap filling limit voltage V of the perovskite film in the control group. TFL(0.46V, 0.79V) are low, which indicates that the defect state density in the perovskite film of the embodiment of the present application is lower than that in the perovskite film of the control group. The perovskite film of the embodiment of the present application is beneficial to improving the PSC efficiency.

[0114] See also Fig.11 In the figure, the horizontal axis is voltage (unit V), and the vertical axis is current density (unit mA / cm 2 ),from Fig.11 As can be seen from the left figure, the open circuit voltage V OC , short circuit current density J SC , fill factor FF, and photoelectric conversion efficiency PCE are 1.169V and 24.98mA / cm 2 , 81.05%, 23.67%, the open circuit voltage V OC , short circuit current density J SC , fill factor FF, and photoelectric conversion efficiency PCE are 1.140V and 24.31mA / cm 2 , 78.66%, 21.80%. Fig.11 As can be seen from the right figure, according to the current density-voltage curves of the perovskite solar cell under the forward scan and reverse scan states, it can be determined that the hysteresis of the perovskite solar cell (the embodiment of the present application and the control group) is relatively small.

[0115] See also Fig.12 In the left figure, the horizontal axis is wavelength (in nm), and the vertical axis is external quantum efficiency (Externa lQuantum Efficiency, EQE, %). Fig.12 As can be seen from the left figure, the EQE of perovskite solar cells is the highest for light in the range of 450-750nm. With the increase of wavelength in the range of 300nm-450nm, the EQE increases rapidly, and with the increase of wavelength in the range of 750-900nm, the EQE decreases rapidly. SC It increases gradually. At 800-900nm, the short-circuit current density J SC The external quantum efficiency EQE represents the ability of each incident photon to be converted into electrons transmitted to the external circuit, expressed as a percentage. The external quantum efficiency EQE spectrum technology can be used to analyze the current loss of perovskite solar cells.

[0116] See also Fig.12 In the middle figure, the horizontal axis is time (unit s), and the vertical axis is current density and PCE. Fig.12As can be seen from the middle figure, within the range of 0-300s, the current density and PCE of the perovskite solar cell are basically stable, wherein the short-circuit current density J of the perovskite solar cell of the embodiment of the present application is SC and PCE are 22.72 mA / cm 2 , 23.17%, the short-circuit current density J of the perovskite solar cell in the control group SC and PCE are 22.11 mA / cm 2 , 21.67%.

[0117] See also Fig.12 In the right figure, the horizontal axis is time (unit: h), and the vertical axis is the normalized PCE. Fig.12 It can be seen from the right figure that in the range of 0-650h, the homogenized PCE of the perovskite solar cell (the embodiment of the present application and the control group) gradually decreases, wherein at any time point in the range of 0-650h, the homogenized PCE of the perovskite solar cell of the embodiment of the present application is greater than the homogenized PCE of the perovskite solar cell of the control group; around 650h, the homogenized PCE of the perovskite solar cell of the embodiment of the present application is 91.8%, and the homogenized PCE of the perovskite solar cell of the control group is 82.3%.

[0118] See also Fig.13 , the horizontal axis is the aging time of the perovskite precursor solution (in days), the vertical axis is PCE (%), the left figure is the perovskite precursor solution of the control group, and the right figure is the perovskite precursor solution of the embodiment of the present application. From the left and right figures, it can be seen that the PCE of the perovskite precursor solution of the control group decreased from about 21% to about 10% from the 0th day to the 28th day, and decreased by about 11% in 28 days; the PCE of the perovskite precursor solution of the embodiment of the present application decreased from about 22% to about 20% from the 0th day to the 28th day, and decreased by about 2% in 28 days. Obviously, the perovskite precursor solution of the embodiment of the present application is more stable and has a longer shelf life.

[0119] The preferred embodiments of the present application are described above with reference to the accompanying drawings, but the scope of the present application is not limited thereby. Any modification, equivalent substitution and improvement made by a person skilled in the art without departing from the scope and essence of the present application shall be within the scope of the present application.

Claims

1. A method for preparing a perovskite material, characterized in that: The preparation method comprises: According to the component Cs of the perovskite material 0.05 FA 0.89 MA 0.06 Pb(I 0.94 Br 0.06 )3, determining a plurality of substances and their contents for synthesizing the perovskite material; Dissolving the plurality of substances in an organic solvent to obtain a first solution; The perovskite material is obtained from the first solution by a temperature inversion crystallization method.

2. The preparation method according to claim 1, characterized in that: The plurality of substances include: PbI2, FAI, MABr, PbBr2 and CsI; And / or, the organic solvent comprises GBL and formic acid.

3. The preparation method according to claim 1, characterized in that: Before obtaining the perovskite material from the first solution by the inversion crystallization method, the method includes: Filtering the first solution using a nylon filter membrane; The method of obtaining the perovskite material from the first solution by a temperature inversion crystallization method comprises: The perovskite material is obtained from the filtered first solution by a temperature inversion crystallization method.

4. The preparation method according to claim 3, characterized in that: The method of obtaining the perovskite material from the filtered first solution by the inversion crystallization method comprises: keeping the filtered first solution in an oil bath at a preset temperature until the perovskite crystals are completely precipitated; The precipitated perovskite crystals are washed and then dried; The dried perovskite crystals are ground into powder and further dried to obtain powdered perovskite crystals.

5. A perovskite solar cell, characterized in that: The perovskite light absorption layer of the perovskite solar cell comprises the perovskite material prepared according to any one of claims 1-4.

6. The perovskite solar cell according to claim 5, characterized in that: The electron transport layer of the perovskite solar cell includes a SnO2 electron transport layer, and / or the hole transport layer of the perovskite solar cell includes a Spiro-OMeTAD hole transport layer.

7. A method for preparing a perovskite solar cell, characterized in that: The preparation method comprises: Providing a transparent conductive glass substrate; Preparing an electron transport layer on the transparent conductive glass substrate; A perovskite light absorption layer is prepared on the electron transport layer using a perovskite precursor solution, wherein the perovskite precursor solution is prepared using the perovskite material prepared according to any one of claims 1 to 4; Preparing a hole transport layer on the perovskite light absorption layer to obtain a prefabricated device; A metal electrode is prepared on the prefabricated device to obtain the perovskite solar cell.

8. The preparation method according to claim 7, characterized in that: The electron transport layer comprises a SnO2 electron transport layer; and / or the hole transport layer comprises a Spiro-OMeTAD hole transport layer; and / or the metal electrode comprises a gold electrode.

9. The preparation method according to claim 7, characterized in that: Before preparing the perovskite light absorption layer on the SnO2 electron transport layer using the perovskite precursor solution, the method comprises: The perovskite precursor solution is obtained by configuring the perovskite material prepared according to any one of claims 1 to 4.

10. The preparation method according to claim 9, characterized in that: The perovskite precursor solution is prepared by using the perovskite material prepared according to any one of claims 1 to 4, comprising: The perovskite material prepared according to any one of claims 1 to 4 and MACl are dissolved in a mixed solvent of DMF and DMSO to obtain the perovskite precursor solution.

Citation Information

Patent Citations

  • Preparation method of high-quality large-size organic-inorganic hybrid perovskite single crystals

    CN108754609A

  • Defect-free perovskite film, preparation method thereof, and application thereof

    CN110112300A

  • Organic-inorganic hybrid perovskite powder and preparation method and application thereof

    CN111785838A

  • Narrow-band-gap alloy perovskite microcrystal as well as preparation method and application thereof

    CN113604881A

  • Perovskite thin film, preparation method thereof and perovskite solar cell

    CN116193957A